2016
DOI: 10.3389/fimmu.2016.00376
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle and Gestational Age-Dependent Expression of Members of the Interleukin-36 Subfamily in a Semi-Allogeneic Model of Infected and Non-Infected Murine Pregnancy

Abstract: The IL-36 subfamily is a recently described group of cytokines with pro-inflammatory behavior, comprising three agonists (α, β, and γ), its receptor (R), and one antagonist (Ra). The expression and function of IL-36 subfamily members in the estrous cycle in healthy and infected pregnancy has not been described. We evaluated mRNA and protein expression of IL-36 family members during the estrous cycle, implantation, fetal development, and post-labor periods in a model of allogenic pregnancy in mice. We also expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…We extend these findings here in the context of a highly relevant STI pathogen, HSV-2. Consistent with a recent clinical report, we found that HSV-2 robustly induces IL-36γ [29]. Furthermore, we found that pretreatment with IL-36γ significantly decreased vaginal viral replication in vitro .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We extend these findings here in the context of a highly relevant STI pathogen, HSV-2. Consistent with a recent clinical report, we found that HSV-2 robustly induces IL-36γ [29]. Furthermore, we found that pretreatment with IL-36γ significantly decreased vaginal viral replication in vitro .…”
Section: Discussionsupporting
confidence: 92%
“…In the upper female reproductive tract it has been shown that Listeria monocytogenes infection robustly induced the IL-36 cytokines in the uteri of pregnant mice, however, the impact of the IL-36 cytokines on infection and pregnancy is still unclear [29]. Recently, our laboratory measured increased levels of IL-36γ in cervicovaginal lavages (CVLs) from cervical cancer patients [30].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of bacterial and viral infections impairs trophoblast invasion and disrupts endothelial tubulogenesis ([ 14 , 15 ] and reviewed in [ 16 ]). Furthermore, our previous report showed enhanced expression of IL-36 members in murine uterine tissue infected by Listeria monocytogenes [ 11 , 12 , 17 ]. To assess the association of microbial components and IL-36 cytokines in trophoblast cells, the effect of LPS and poly I:C stimulation was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the IL-36 family in pregnancy remains largely unknown. In mice, high expression of IL-36 was reported in the uterus at estrus stage and during labor, and is highly induced by Listeria monocytogenes, demonstrating its role in inflammation and maternal immune response to pathogens [ 11 , 12 ]. In humans, a recent report demonstrated enhanced levels of IL-36Ra in plasma samples of pregnant compared to non-pregnant women, and decreased IL-36Ra levels in extracellular vesicles from preeclampsia versus healthy placentas [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deregulated expression of IL-36 cytokines could be associated with the development of pregnancy complications. Using a mouse model of pregnancy infected by Listeria monocytogenes, we described a differential and strong mRNA and protein expression of IL-36 (α, β, γ) as well as IL-36Ra and IL-36R in the uterus [141]. We also observed that high levels of IL-36 cytokines in infected animals enhances inflammatory activity, associated with a high ratio of fetal resorption [142].…”
Section: Il-36 Cytokines In Female Reproductive Tissues and Pregnancymentioning
confidence: 99%